2017
DOI: 10.1073/pnas.1706778114
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective inhibition of IMPDH2 provides the basis of antineuroinflammation therapy

Abstract: Inosine monophosphate dehydrogenase (IMPDH) of human is an attractive target for immunosuppressive agents. Currently, smallmolecule inhibitors do not show good selectivity for different IMPDH isoforms (IMPDH1 and IMPDH2), resulting in some adverse effects, which limit their use. Herein, we used a small-molecule probe specifically targeting IMPDH2 and identified Cysteine residue 140 (Cys140) as a selective druggable site. On covalently binding to Cys140, the probe exerts an allosteric regulation to block the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 33 publications
4
91
0
Order By: Relevance
“…The vehicle and handelin-coupled beads were subsequently mixed with cell lysates and then incubated overnight at 4 °C. The bead-captured proteins were obtained by incubating the mixture and separated to 10% SDS-PAGE, visualized by silver staining and then identified by LC-MS/MS using a nano-HPLC-tandem LTQ-Orbitrap Velos pro mass spectrometer (Thermo Fisher Scientific) as our previous study reported ( Liao et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vehicle and handelin-coupled beads were subsequently mixed with cell lysates and then incubated overnight at 4 °C. The bead-captured proteins were obtained by incubating the mixture and separated to 10% SDS-PAGE, visualized by silver staining and then identified by LC-MS/MS using a nano-HPLC-tandem LTQ-Orbitrap Velos pro mass spectrometer (Thermo Fisher Scientific) as our previous study reported ( Liao et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Then, the GSH-handelin complex was analyzed by liquid chromatography coupled with hybrid triple quadrupole-linear ion trap mass spectrometer (LC-Q-trap-MS) method. The protocol was according to previous report ( Liao et al, 2017 ) excepting that the mobile phase consisting of water (0.1% formic acid, A) and acetonitrile (B), was delivered at a constant flow rate of 0.4 mL/min with a gradient elution of 5–20% B at 0–1 min, 20–100% B at 1–3 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this strategy, a series of targets for active components of TCM have been successfully identified. For example, Tu research group constructed probe for sumitone [47] and chrysanthema lactone [48], successively identified the target of sumitone a as inosine monophosphate dehydrogenase 2 (IMPDH2), and the target of chrysanthema lactone with anti-inflammatory effect was heat shock protein 70 (HSP70). All of them revealed the mechanism of action for active components in TCM from the origin.…”
Section: Discussionmentioning
confidence: 99%
“…IMPDH plays a particularly important role in the immune response, where T-cell activation is dependant on increased production of purine nucleotides, and is associated with IMPDH filament assembly (Gu et al 2000; Zimmermann et al 1998; Duong-Ly et al 2018; Calise et al 2018). As a result, IMPDH is the target of several drugs used in immunosuppressive treatment of both autoimmune disease and organ transplant rejection, and is considered a promising target for antineoplastic agents (Shu & Nair 2008; Liao et al 2017; Bergan et al 2016).…”
Section: Discussionmentioning
confidence: 99%